(untitled) (Ágora de Heterodoxias, 2023)
This paper discusses the conclusive observation of Fernando Calderón and Manuel Castells in their book La nueva América Latina, about the economic development experience lived for the region between 2003 and 2013. Their named this experience “new developmentalism”. The alternative narrative proposed in the essay suggests that there was no developmental moment in the region, but rather a sudden and prolonged boom in foreign income provided by the generalized rise in the prices of basic products, which was used by the emerging political class to increase public spending and finance the constitution of a clientelistic political base on which to sustain his own pre-eminence and conditions of possibility in the face of the electoral cycle. The eleven years of growth based on the monetization of external income did not generate changes in the diversification of the economic base and in the expansion of the export basket, and much less growth in labor productivity to sustain the expansion of the internal market and exports.